2007
DOI: 10.1038/sj.onc.1210348
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 promotes human glioma progression through potentiating the activity of the HGF/SF autocrine pathway

Abstract: Neuropilin-1 (NRP1) functions as a coreceptor through interaction with plexin A1 or vascular endothelial growth factor (VEGF) receptor during neuronal development and angiogenesis. NRP1 potentiates the signaling pathways stimulated by semaphorin 3A and VEGF-A in neuronal and endothelial cells, respectively. In this study, we investigate the role of tumor cell-expressed NRP1 in glioma progression. Analyses of human glioma specimens (WHO grade I-IV tumors) revealed a significant correlation of NRP1 expression wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
155
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(161 citation statements)
references
References 15 publications
2
155
0
Order By: Relevance
“…The role of Sema3A in glioblastoma dispersal T Bagci et al Hu et al, 2007;Staton et al, 2007;Vales et al, 2007). In addition to its role as a Sema3A receptor, neuropilin-1 is a co-receptor for a specific isoform of VEGF165 and guides endothelial cell migration during vascular morphogenesis (Soker et al, 1998;Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of Sema3A in glioblastoma dispersal T Bagci et al Hu et al, 2007;Staton et al, 2007;Vales et al, 2007). In addition to its role as a Sema3A receptor, neuropilin-1 is a co-receptor for a specific isoform of VEGF165 and guides endothelial cell migration during vascular morphogenesis (Soker et al, 1998;Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The role of neuropilin-1 in tumors has been mostly studied in the context of its interaction with VEGF165 and related to tumor angiogenesis and tumor cell survival (Miao et al, 2000;Bachelder et al, 2001). A recent study suggested that neuropilin-1 contributes to tumor progression by potentiating the activity of hepatocyte growth factor as well (Hu et al, 2007). However, the role of neuropilin-1 in tumor progression has not been studied in the context of its Sema3A interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because epithelial cells are the primary source of VEGF in lung lavage, an alternative explanation linking conditional epithelial Nrp1 deletion and decreased lavage VEGF concentrations in CS-exposed CCSPrtTA/tetO-Cre/Nrp1 flox/flox mice could be that enhanced epithelial cell death decreases VEGF production. Furthermore, although several investigators have demonstrated that the effects of Nrp1 on cell proliferation and death may depend on how this receptor modulates the balance between VEGF and Sema3 signaling (17,26), other studies also demonstrate that Nrp1 may alter cell survival independent of its effects on VEGFR activation (22,(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NRP1 overexpression was related to poor prognosis in human gliomas and with the malignancy of astrocytic tumours (Osada et al, 2004;Hu et al, 2007). Increased expression of NRP1 has also been detected in tumour cells from clinical glioma samples, suggesting a link between NRP1 expression and glioma malignancy (Ding et al, 2000).…”
mentioning
confidence: 99%